Transport through liquid membranes containing omeprazole and lansoprazole - Nagappa, A.N.; Pandi, P.V.; Girish, R.K.; Shanmukh, I. (National Institute of Science Communication and Information Resources, CSIR, 2002)
Oseprazoe and lansoprazole, the therapeutically important drugs belonging to proton pump inhibitor category are extensively used in the treatment of gastric ulcers. Transport through liquid membranes generated by these drugs in lecithin-cholesterol mixture in series with a supporting membrane has been studied. The data obtained show tire formation of liquid membrane in series with tie supporting membrane, Transport of canons, chloride and bicarbonate ions in the presence liquid membranes generated by omeprazole and lanzoprazole indicate the modification in the permeability of various permeants.